Soft tissue liposarcomas - Chiossoni, Martha (Cirugía del Uruguay, 1973)
Tumors in soft parts comprise !iposarcomas, which are second in frequency, evolution and prognosis. Evolution is slow and they seldom result in metastasis. Their therapy is almos! exclusively surgical.